Studi Tentang Seleksi Karyawan CV Sumber Jaya Lestari Medan - Weny (Forum Kerjasama Pendidikan Tinggi, 2021)
The purpose of this research is to find out about the employee selection process applied in CV. Sumber Jaya Lestari, Medan. The theory states that the selection process is sorted into several stages, namely: Acceptance of Application Letters, Employee Selection Tests, Interviews, Reference Checks, Health Tests, Supervisor Interviews, Job Demos, Test Decisions. The method used in this research is descriptive qualitative method. The data collection technique used by the author is a structured interview technique. Findings from the manager's and supervisor's research stated that they felt that the selection process was good enough, however, the medical tests only looked at the physical appearance of prospective employees and were not assessed by skilled medical personnel. The results obtained from this research are (1) The company has screened applicants by filtering them according to the company's needs for vacant positions and areas of the company applied for by prospective employees, (2) The company provides tests to prospective employees as a form of selection, namely only only an academic test. (3) The company always conducts initial interviews quickly, because the application letter has been attached quite completely regarding the person of the job applicant. So there are not many things that need to be interviewed again (4) The company always evaluates the background of job applicants as a form of selection, evaluation of the background of job applicants is carried out through interviews when first called for an interview. (5) The company never conducts medical tests because usually the health of job applicants is assessed during interviews by looking at the physical employees (6) The company has never conducted in-depth interviews which are usually done by company managers because this is considered to only repeat activities that have been carried out which are considered a waste of time course. (7) The company has never carried out a Demo Job since the company started because it was too risky in terms of finances. (8) The company always provides information on whether or not prospective applicants who apply for work in the company are accepted.